2008
DOI: 10.1186/1471-2199-9-93
|View full text |Cite
|
Sign up to set email alerts
|

Novel RNA-binding properties of the MTG chromatin regulatory proteins

Abstract: Background: The myeloid translocation gene (MTG) proteins are non-DNA-binding transcriptional regulators capable of interacting with chromatin modifying proteins. As a consequence of leukemia-associated chromosomal translocations, two of the MTG proteins, MTG8 and MTG16, are fused to the DNA-binding domain of AML1, a transcriptional activator crucial for hematopoiesis. The AML1-MTG fusion proteins, as the wild type MTGs, display four conserved homology regions (NHR1-4) related to the Drosophila nervy protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…This previous study also indicated that HDAC1 enhances miRNA processing via deacetylation of Drosha/DGCR8 [27]. Thus, based on the observations that ETO2 directly associates with HDAC1 [10] and exerts RNA binding properties [23], we speculate that ETO2 may promote processing of a subset of miRNAs, leading to transcriptional/translational repression. However, we cannot exclude the possibility that ETO2 directly represses other factors, which might lead to the increased pre‐miRNA transcripts, which warrants further analyses.…”
Section: Resultssupporting
confidence: 57%
“…This previous study also indicated that HDAC1 enhances miRNA processing via deacetylation of Drosha/DGCR8 [27]. Thus, based on the observations that ETO2 directly associates with HDAC1 [10] and exerts RNA binding properties [23], we speculate that ETO2 may promote processing of a subset of miRNAs, leading to transcriptional/translational repression. However, we cannot exclude the possibility that ETO2 directly represses other factors, which might lead to the increased pre‐miRNA transcripts, which warrants further analyses.…”
Section: Resultssupporting
confidence: 57%
“…Prdm14 is a sequence-dependent DNA-binding protein that binds many genomic loci in mESCs, corresponding primarily to distal regulatory elements, whereas ETO proteins do not contain domains implicated in direct DNA sequence recognition ( Rossetti et al, 2004 , 2008 ). To examine whether Mtgr1 is brought to genomic targets occupied by Prdm14, we performed Mtgr1 ChIP coupled with high-throughput DNA sequencing (ChIP-seq) from wt mESCs, FH-Prdm14 overexpressing mESCs, and as a control for antibody specificity, Mtgr1 −/− mESCs (generation of which is described in more detail later), cultured for 5 days under serum+leukemia inhibitory factor (LIF) conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was mainly characterized by its four nervy homology regions (NHRs). These NHRs define the domains of Runx1t1 that mediate interactions with other proteins, such as the N-CoR/mSin3A/ HDACs, to form a co-repressor complex for transcription repression [17,30,31]. During early adipogenesis, Runx1t1 may act as an inhibitor of C/EBPβ contributing to its characteristically delayed activation, thereby block transcription of its downstream genes (such as PPARγ), inhibiting preadipocyte differentiation [32].…”
Section: Discussionmentioning
confidence: 99%